Diversity of Vascular Plants at Tan Trao Historical Site, Tuyen Quang Province - Cong Ba, Do; Ngoc Cong, Le; Dong Tan, Le (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4773, 2018)
Abstract: The flora at Tan Trao Historical site (Tuyen Quang province) is quite rich and varied. The study identified 726 species, 462 genera, 137 families of 6 vascular plant divisions. The Magnoliophyta is the largest division with 669 species (92.15%), 427 genera (92.42%) and 115 families (83.94%), followed by Polypodiophyta with 39 species (5.37%), 25 genera (5.41%) and 13 families (9.49%). Psilotophyta, Lycopodiophyta, Equisetophyta and Pinophyta are the smallest divisions. The Magnoliophyta is the most diversified with 5.82 species per family and an average of 3.71 genera per family. The survival spectrum of Tan Trao Historical site’s flora was determined as SB = 73.55 Ph + 3.17 Ch + 9.78 He + 8.40 Cr + 5.10 Th. By use-value, medicinal plants are the most abundant with 470 species, followed by timber trees, eatable plants, ornamental plants, plants for animal feed, plants for attar, fiber plants, plants for handicrafts, plants for dyes, and plants for sap, with 188, 142, 99, 64, 50, 28, 11, 5, and 3 species, respectively. Keywords : Tuyen Quang, Tan Trao Historical site, flora, life form. References [1] Ban Quản lý Khu di tích lịch sử Tân Trào, Hồ sơ quy hoạch tổng thể bảo quản, tu bổ, phục hồi, và phát huy giá trị di tích Quốc gia đặc biệt Tân Trào tỉnh Tuyên Quang gắn với phát triển du lịch đến năm 2025, Tuyên Quang 2015. [2] Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, Nxb. Đại học Quốc gia, Hà Nội, 2007. [3] Hoàng Chung, Các phương pháp nghiên cứu quần xã thực vật, Nxb. Giáo dục, Hà Nội, 2008. [4] Phạm Hoàng Hộ, Cây cỏ Việt Nam (quyển I, II, III), Nxb. Trẻ, Tp HCM, 1999, 2003, 2000. [5] Nguyễn Tiến Bân (chủ biên) và cs. Danh lục các loài thực vật Việt Nam (tập 2-3), Nxb. Nông nghiệp, Hà Nội, 2003-2005. [6] Brummitt RK., Vascular plant families and genera, Royal Botanic Gardens, Kew, 1992. [7] Raunkiaer C., Plant life forms, Claredon, Oxford, 1934. [8] Trần Đình Lý, 1900 loài cây có ích ở Việt Nam, Nxb. Thế giới, 1993. [9] Triệu Văn Hùng (chủ biên) và cs, Lâm sản ngoài gỗ ở Việt Nam, Nxb. Bản đồ, Hà Nội, 2007. [10] Võ Văn Chi, Từ điển cây thuốc Việt Nam, tập 1, 2, Nxb. Y học, Hà Nội, 2012.